Accounting Cultural Values And Real Earnings Management In Companies Listed In Nigerian Exchange Group - Ogan, Tamunokonbia Promise; Nwaobia, Appolos Nwabuisi; Ajibade, A. T. (CV ODIS, 2025)
This study examined the influence of accounting cultural value on real earnings management practice in companies listed in the Nigerian Exchange Limited. The study adopted the survey research design. The population was 1,192 chartered accountants working in companies listed in the Nigerian Exchange Group. The sample size of 304 was determined using the Taro Yemani formula. The study adopted stratified and random sampling techniques. A structured and validated questionnaire was employed to gather data. The findings of this study suggest that accounting cultural values of conservatism, harmony, and egalitarianism do not have a statistically significant effect on real earnings management in companies listed on the Nigerian Exchange Group. Hence, the study concludes that accounting cultural values do not statistically affect real earnings management in companies listed on the Nigerian Exchange Group Limited. The study therefore recommended that regulatory bodies such as the Financial Reporting Council of Nigeria, the Security Exchange Commission, and the Nigerian Exchange Group Limited should enhance their monitoring and enforcement mechanisms to forestall real earnings management.